Front Cover: When Two Become One: Conformational Changes in FXR/RXR Heterodimers Bound to Steroidal Antagonists (ChemMedChem 4/2023). (15th February 2023) - Díaz‐Holguín, Alejandro; Rashidian, Azam; Pijnenburg, Dirk; Monteiro Ferreira, Glaucio; Stefela, Alzbeta; Kaspar, Miroslav; Kudova, Eva; Poso, Antti; van Beuningen, Rinie; Pavek, Petr; Kronenberger, Thales
Abstract : The Front Cover features the farnesoid X receptor (FXR) which is a nuclear receptor with a role in regulating bile acid synthesis and cholesterol homeostasis. This work studies the ligand‐mediated FXR activation and heterodimerization using microsecond timescale molecular dynamics simulations. Recently reported FXR antagonists and well stablished agonists were investigated. Changes in the heterodimerization interface induced by antagonists prevent recruitment of co‐regulatory elements. These results provide insights into their conformational changes and show what happens when two nuclear receptors become one system. More information can be found in the Research Article by Alejandro Díaz‐Holguín, Azam Rashidian, Thales Kronenberger et al.